Press Release Strategy As A Public Relations Instrument In Building Corporate Reputation: A Conceptual Study At PT Astra International Tbk - Tiyas Sholikhatul Maghfuroh; Dewi Puspita; Dela Ayu Nabila; Pramudya Ibnu Subrata (CITACONOMIA : Economic and Business Studies, 2026)
This conceptual article examines the strategic role of press releases in the formation of corporate reputation and institutional legitimacy within the context of public companies. Amidst increasing demands for transparency and accountability, this study redefines the press release not merely as a technical information tool, but as a sophisticated managerial mechanism for stakeholder engagement. By integrating Excellence Theory, Stakeholder Theory, and Legitimacy Theory, a conceptual model is proposed to illustrate how specific communication strategies—encompassing information transparency, strategic message framing, and the inclusion of a managerial voice—act as primary determinants of stakeholder perception. The analysis emphasizes that a consistent and data-driven corporate narrative reduces information asymmetry and reinforces the organization's economic, social, and moral legitimacy. This research contributes to the strategic public relations literature by positioning the press release as a "strategic bridge" that facilitates the construction of reputation as a valuable intangible asset, particularly within the dynamic regulatory environments of emerging markets such as Indonesia. Ultimately, the article provides a robust analytical foundation for future empirical studies to validate the causal relationships between formal corporate communication practices and long-term organizational sustainability in the global capital market.